Kenyan English idiomatic expressions: They may sound frequent but that’s not what corpus data show - Otiso, Zipporah (Linguistik Online, 2024)
Keen observers of Kenyan English usage will agree that idiomatic expressions such as put into consideration, rather than take into consideration, are certainly common in daily usage. The author of this paper set out to establish if that was indeed the case by having a sample of 122 respondents, all fourth-year university students, to choose between put and take. 77% of them chose put, which suggests that the expression put into consideration is indeed quite familiar to Kenyan English speakers. It was tested alongside another 19 idiomatic expressions. 17 out of the 20 were found to be familiar, though to varying degrees. But this familiarity was not reflected in corpus data from the International Corpus of English and the Corpus of Global Web-based English, where they were found to be rare. The same corpus data showed that this familiarity of the 20 expressions to Kenyan English speakers did not mean that they used them more frequently than their Standard International English counterparts. For example, the data showed that the “less familiar” take into consideration had more tokens in the Kenyan English components of the two corpora than the “more familiar” put into consideration. Nevertheless, the paper concludes that so-called Kenyan English idioms can still be claimed to be typical of Kenyan English, since they are practically absent from e. g. British English, its colonial ancestor.